1995
DOI: 10.1002/jctb.280640208
|View full text |Cite
|
Sign up to set email alerts
|

Flat‐sheet and hollow fiber membrane bioreactors: A study of the kinetics and active site conformational changes of immobilized papain including sorption studies of reaction constituents

Abstract: Papain, a sulfhydryl protease has been immobilized on flat-sheet modified polysulfone membranes and hydroxyethyl cellulose coated polyethersulfone hollow fibers. Amidase activity of the enzyme in solution and on the membranes has been assayed. Immobilized papain on the modified polysulfone membrane and the hollow fibers retains 12% and 25% of its activity (with 1 mmol dm-3 substrate) in solution, respectively. Loading experiments revealed decreased activity on the modified polysulfone membrane with increased e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The result showed that native trypsin had a constant specific initial velocity of 0.31 mmol mg −1 min −1 in concentrations ranging from 1.75 to 16.75 μg/cm 3 . An increase in the immobilized amount led to the crowding of trypsin molecules in the grafted PAA layers, resulting in spatial restrictions, blocking of active sites, and/or denaturation of enzymes 2, 45. An alternative explanation is that multipoint attachment of trypsin molecules through peptide bonding would decrease their conformational flexibility in the vicinity of the active sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that native trypsin had a constant specific initial velocity of 0.31 mmol mg −1 min −1 in concentrations ranging from 1.75 to 16.75 μg/cm 3 . An increase in the immobilized amount led to the crowding of trypsin molecules in the grafted PAA layers, resulting in spatial restrictions, blocking of active sites, and/or denaturation of enzymes 2, 45. An alternative explanation is that multipoint attachment of trypsin molecules through peptide bonding would decrease their conformational flexibility in the vicinity of the active sites.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, many investigators have attempted to develop various methods for decreasing the expense and increasing the stability of enzymes. Recently, considerable attention has been devoted to developing technologies suitable for using immobilized enzymes in an aqueous medium 1–4. As easily removable and reusable biocatalysts, immobilized enzymes offer a considerable number of advantages: increased shelf life, operational simplicity, and thermal and pH stabilities 5–10…”
Section: Introductionmentioning
confidence: 99%
“…The membrane matrix was composed of poly(ether)sulfone blended with polyacrolein to provide aldehyde functionality. The average pore size of the membrane was 0.45 m, and the thickness of the membrane was 152 m. The surface area of the membrane was determined by nitrogen gas adsorption studies using the Brunauer-Emmett-Teller pore (BET) isotherm, to be 9 m 2 /g (Ganapathi et al, 1995). The other membrane used for enzyme immobilization was purchased from Whatman (product # 6872-1703, Actidisk), and was composed of poly(vinyl chloride) (PVC) sheets with embedded aldehyde-functionalized silica (approximately 65% silica) particles to provide functionality for enzyme attachment.…”
Section: Immobilization Supportsmentioning
confidence: 99%
“…The rate of reaction was analyzed by measuring the amount of the product p-nitroaniline in the permeate. There is a significant amount of product sorbed to the membrane which, if not accounted for, can result in erroneous kinetic data (Ganapathi et al, 1995). Hence, the amount of product adsorbed on the membrane that is in equilibrium with the product in the reaction mixture was added up to give the total amount of product formed in the reaction.…”
Section: Wild-type Subtilisinmentioning
confidence: 99%
“…In addition, urease immobilized on the ePTFE‐ g ‐PHEMA films with lower grafted amounts had higher relative activity. As urease was also immobilized on grafted PHEMA chains in the inside of the grafted layer at higher grafted amount, diffusion of urea molecules into the grafted layers was suppressed, resulting in a decrease in the relative activity 19, 22, 43…”
Section: Resultsmentioning
confidence: 99%